Diversity of Hesperids (Lepidoptera: Hesperiidae) in agroecosystems of Lara State, Venezuela (Bioagro, 2020)
The hesperids or skippers are diurnal butterflies whose role of their species as indicators of the conservation level of ecosystems is recognized. With the objective of obtaining information on new records of these butterflies, field trips were made to several localities of Lara State, Venezuela, from 2013 to 2016. Adults were collected using insect nets, while immature stages were obtained manually together with parts of the associated plant. After collection, samples were taken to the Entomology Research Laboratory at Universidad Centroccidental Lisandro Alvarado. Species diversity was estimated through the use of alpha and Beta indices. The faunal composition was also illustrated through Venn diagram. From the taxonomic review, it was possible to identify 236 specimens, which were grouped into 3 subfamilies, 11 genera and 7 species as follow. Hesperiinae: Hylephila phyleus (Drury, 1773), Perichares (Scudder, 1872), Panoquina Hemming, 1934 y Wallengrenia Berg, 1897. Pyrginae: Antigonus Hubner, 1819, Autochton zarex Hubner, 1818, Autochton Hubner, 1823, Chiodes castillus Cramer, 1779, Heliopetes macaira Reakirt, 1864, Pyrgus Hubner, 1819, Pyrgus orcus Stoll, 1780, Urbanus proteus (Linnaeus, 1758), U. dorantes (Stoll, 1790) y Pyrrhopyginae: Pyrrhopyge  Hubner, 1819. The locality of Río Claro presented the highest alpha and Beta diversity value, followed by Tarabana and Carorita. The species with the highest number of individuals was U. proteus, which has been reported by other authors as a pest in legumes.Bosque seco tropical
Keywords: Biological indicators; dry tropical forest; jumping butterflies; mountain forests